Protective effect of sweet basil extracts against vitamin C degradation in a model solution and in guava juice - Thanyaporn Siriwoharn (2018)
© 2018 Wiley Periodicals, Inc. Vitamin C is a water-soluble antioxidant used in the food industry despite its well-known instability. This study aimed to investigate the effectiveness of sweet basil methanolic and ethanolic extracts in delaying vitamin C degradation in a model solution and in guava juice during storage (25, 35, and 45 °C). Solutions containing methanolic extracts (0.5–2%) had higher vitamin C content than controls at all times and temperatures. The protective effect depended on extract concentration, storage time, and storage temperature (p <.01). Ethanolic extracts were only significantly beneficial at 35 and 45 °C (p <.05). At these temperatures, methanolic extracts were better at preserving vitamin C in the model solution and the guava juice. The vitamin C was 38.6 and 45.3% higher than the control with a 3% methanolic extract in guava juice after 1 week at 35 and 45 °C, respectively. Practical applications: Vitamin C has been used extensively in food, supplement, pharmaceutical, and cosmetic industries as a nutrient as well as a potent antioxidant. The major limitation is its instability towards heat, light, and oxidation. This study offered a natural solution to vitamin C preservation in foods. It also provided basis for future development of natural preservative for oxidation sensitive compounds in foods and supplement products.